Design And Development Symmetrical Absorptive Mode Single Pole Double Throw (SPDT) Switch Design For WiMAX Application - Lim , Chee Chiang (2010)

(untitled)
The wireless communications market has gone through a tremendous incline of paradigm shift in the last several years. Broadband technology via WiMAX has rapidly become an established, global commodity required by a high percentage of the population. The persistent growth in WiMAX applications introduces tremendous challenges on component manufacturing to speed up new product release in shorter time to market. As a result, there is an increasing demand for high power with low insertion loss, high isolation and broadband PIN Diode switches for WiMAX basestation application.